Commodities and the Market Price of Risk - Roache, Shaun (IMF Working Papers; Working Paper, 2008)
Commodities are back following a stellar run of price performance, attracting financial investor attention. What are the fundamental reasons to hold commodities? One reason is the exposure offered to underlying risk factors. In this paper, I assess the macro risk exposure offered by commodity futures and test whether these risks are priced, using Merton's (1973) intertemporal capital asset pricing model for a sample of commodity prices covering the period January 1973 - February 2008. I find that commodity futures offer a hedge against lower interest rates and that investors are willing to accept lower expected returns for this position. Although some commodities are also a hedge against U.S. dollar depreciation, this risk is not priced.